Lumkani : rapid detection of fires in informal settlements - Van der Hoven, Chris; Townsend, Stephanie (London : Wits Business School, 2018)
In mid-2017, David Gluckman, director of Lumkani, contemplated the company's next strategic move. Lumkani, a South African start-up company, manufactured an early-warning fire detection system designed for shack-dwellers in informal settlements, with the aim of reducing deaths and damage due to fire in those communities.Lumkani had already demonstrated its value locally, now it needed to grow the business internationally. Given that 72% of urban dwellers in sub-Saharan Africa lived in so-called slums, Africa, particularly East Africa and the Southern African Development Community (SADC) countries, presented abundant opportunities.But venturing into Africa meant that Gluckman had to consider suitable scaling business models. What would the ideal model be that would allow Lumkani to scale the business, but keep the balance between ownership and control, he wondered? Should he be looking at implementing one business model, or more than one? And, which one would allow him the highest level of penetration in the shortest time possible so as to stay ahead of competitors with alternative technologies?
Originally Published Invan der Hoven, C., & Townsend, S. (2018). Lumkani: Rapid detection of fires in informal settlements. WBS-2017-4. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Gluckman, David; Llumkani; Export marketing -- Africa, Sub-Saharan -- Case studies; Strategic planning -- Africa, Sub-Saharan -- Case studies; International business enterprises -- Africa, Sub-Saharan -- Case studies; Fire detectors -- Marketing -- Africa, Sub-Saharan -- Case studies